The Effect of a Structured Individualized Educational Intervention on Breastfeeding Rates in Greek Women - Theoni Truva (MDPI AG, 2021)
Breastfeeding rates remain extremely low in Greece and women with gestational diabetes mellitus and hypothyroidism may experience additional difficulties. The aim of the study was to investigate the effect of a structured individualized lactation educational intervention by a midwife on increasing breastfeeding rates in women with endocrine disorders and low-risk women compared to women receiving standard care, 24 months after delivery. Two-hundred women made up the study population. Half of them were experiencing endocrine pregnancy disorders and 100 women constituted the low-risk pregnancy standard care control group. Women who were breastfeeding exclusively were significantly higher in the midwifery intervention group with endocrine disorders, namely breastfeeding continued at four months (breastfeeding: 20% vs. 12%, exclusive breastfeeding: 50% vs. 26%, p = 0.0228), and at six months after childbirth (breastfeeding: 54% vs. 28%, exclusive breastfeeding: 32% vs. 12%, p = 0.0011), compared to the standard care control group with endocrine disorder. The low-risk midwifery intervention group breastfed at four months (22% vs. 14%, p = 0.0428) and at six months (52% vs. 26%, p = 0.0018) at higher rates compared to the standard care control group. In addition, exclusive breastfeeding was significantly higher in the low-risk midwifery intervention group at four months (46% vs. 20%, p = 0.0102) and six months (38% vs. 4%, p < 0.0001) compared to the standard care control group. This study was the first attempt of a structured midwifery breastfeeding education in Greece and its major contribution reflects a significant positive impact on breastfeeding rates in terms of duration and exclusivity in women with gestational endocrine disorders as well as in low-risk women, and could possibly be applied and instituted in everyday clinical practice to increase the low breastfeeding rates in Greece.